Preliminary study on new container stacking/storage system due to space limitations in container yard - Abdul Rahman, Noorul Shaiful Fitri; Ismail, Alisha; Lun, Venus Y.H. (Emerald Group Publishing Limited, 2016)
Purpose:The purpose of this study is to introduce a new innovative means of container stacking/storage as a potential solution for overcoming the lack of container yard space. Design/methodology/approach: A qualitative methodology that incorporates questionnaires and interview sessions as the tools is utilised together with an application of new innovation concept.Findings:The proposed system not only allows increased efficiency and effectiveness in handling containers, but also increases the profit margin of ports, as container stacking/storage is tripled in height. Research limitations/implications:This is just the beginning of a preliminary research study that proposes a new container stacking/storage system to address the lack of space in container yards. Therefore, much more work needs to be done in future studies before a solid and concrete decision on the application of this innovative system can be carried out.Practical implications:The practicality of the proposed model means that it can be easily implemented to address space limitation problems in ports. Social implications:The benefits of the results to the local community around ports are a healthier environment, with cleaner air, so that there will be less health issues of the residents and therefore reduced burden on the local health system. This is due to the use of technology that will prevent the expansion of ports that ultimately could lead to deforestation and environmental damage.This technology will also help to preserve the greenery of the area around ports.Originality/value:An innovative model of a container stacking/storage system is presented in this study as a possible solution to the problem.